Canopy habitat area effect on the arthropod species densities in the Azores: pondering the contribution of tourist species and other life histories - Ribeiro, Sérvio P. (2010)
"[…]. We performed a PIAR examining how plant cover area and plant crown structure influence the densities of arthropods in the canopies of one specific island, comparing various distinct natural reserves. Species densities were measured for two functional insect herbivore guilds (sap-sucking and leaf-chewing insects) and the most common predatory assembly in this system (spiders) in three different ways: i) the average number of specimens per plant; ii) the average number of specimens per transect, providing both fine and broad scales of species abundance (see Methods); iii) absolute numbers per reserve. Moreover, we investigated common versus scarce arthropod species distributions between various plant species. […]" (da Introdução)